Silicon carbide thin film deposited by unbalanced magnetron sputtering method - Bae, Kyung-Eun; Chae, Ki-Woong; Park, Jong-Keuk; Lee, Wook-Seong; Baik, Young-Joon (KOREAN INST METALS MATERIALS, 2015)
The effect of sputter target power and substrate bias voltage on the deposition of silicon carbide thin film was investigated. Films were deposited using unbalanced magnetron sputtering method with sintered silicon carbide target connected to a direct current electric power from 50 to 200 W. Ar gas was used as a sputtering gas. The distance between the target and the substrate was 7.5 cm and the deposition pressure was 3 m Torr. We used a Si single crystal wafer as a substrate, which was heated at 450 degrees C. The substrate bias voltage was varied between 0 and -100V. Deposited films consisted of columnar grains with several nm width, which formed a texture whose orientation was influenced by the bias voltage. Most of the grains were crystalline which was confirmed by transmission electron microscopy. The hardness measured by a nano-indentation method showed a super-hardness of about 50 GPa.
Keywords: CHEMICAL-VAPOR-DEPOSITION; MECHANICAL-PROPERTIES; SI FILMS; ELASTIC-MODULUS; A-C; COATINGS; HARDNESS; NANOCOMPOSITES; TEMPERATURE; MEMBRANE